(3efgL GdEOGQI GdYdjG (B:s (3COhGJ Jbjje GdCOGA (B/s - (3Jhajb, YHO GdQMefs ((3GdbGgQI(B: s (3eQcR GdNHQGJ GdegfjI ddEOGQI(B, s, 2004)
(3WQb hCSGdjH Jbjje GdCOGA(B- (3WQb Jbjje GdCOGA GSJbUGA bjGS aYGdjI COGA GdeQDhSjf(B- (3GdeOjQ hGdJWhjQ GdJfXjej(B.s
Keywords: (3GdEOGQIs; (3GdEOGQI GdESJQGJjLjIs